Physical Activity Levels and the Incidence of Type 2 Diabetes: A Cross-Country Analysis Using WHO and World Bank Data - Sahal Hanafi; Ilham Kurniawan; Rafidha Nur Alifah; Ina Monica Firsty; Samsul Arifin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Type 2 diabetes mellitus represents a growing global public health and economic challenge, with incidence rates varying markedly across countries. Physical activity is widely recognized as a protective factor, yet its population-level role remains shaped by socioeconomic conditions, health system capacity, and policy environments. This study examines the relationship between national physical activity levels and the incidence of type 2 diabetes using harmonized cross-country data from the World Health Organization and the World Bank. A quantitative analytical approach was applied to assess associations while accounting for demographic structure, economic development, and institutional factors influencing disease detection and prevention. The findings indicate that countries with higher physical activity prevalence generally exhibit lower diabetes incidence, although this relationship is mediated by inequality, urbanization, and screening coverage. Economic evidence further shows that a significant share of diabetes-related health expenditure is attributable to insufficient physical activity, highlighting the high cost of inaction. Policy analysis underscores that investments in active transport, education, and community-based interventions offer substantial long-term health and economic returns. Overall, the study reinforces physical activity promotion as a globally relevant, cost-effective strategy for reducing type 2 diabetes incidence and advancing sustainable population health.